The Effect of Safety Ridingand Customer Satisfaction on the Company Image of PT. Daya Adicipta Motora Bandung - *Wala Erpurini; Azhar Affandi; Sidik Priadana (Riwayat: Educational Journal of History and Humanities, 2022)
The purpose of this study was to determine the effect of safety riding and consumer satisfaction on the corporate image of PT. Daya Adicipta Motor Bandung. This research was conducted on participants of Safety Riding training at PT. Daya Adicipta Motora Bandung. The sample used is a non-random sample consisting of 195 respondents. This research uses descriptive method with weighting and associative method. Data were collected using a questionnaire. The Likert scale model was tested using validity and reliability tests. The validity test was calculated using the Product Moment formula, while the reliability test was calculated using the Cronbach Alpha technique. Calculations using IBM SPSS Statistics 25.